Guest

please give me the answer of the Last question ... question no. 3..

please give me the answer of the Last question ... question no. 3..
 

Question Image
Grade:12th pass

1 Answers

Vikas
13 Points
one month ago
Let roots are alpha, - alpha, beta 
Sum of roots = alpha - alpha + beta = -a1 
 Beta = -a1     ..... (1) 
alpha (-alpha ) + (-alpha) beta + beta (alpha) = a2
-(alpha)^2 = a2      ..... (2) 
(alpha) (-alpha) (beta) = -a3
-(alpha)^2 (beta) = -a3   ..... (3) 
Using (1) & (2) in (3) we get 
a2(-a1) = -a3 
-a1a2 = -a3 
Therefore 
a1a2 -a3 = 0 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free